’Urf Sebagai Sumber Hukum Islam (Fiqh) Nusantara - Harisudin, M. Noor (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
This paper would like to see how the customs (’urf) became one of source Indonesian Islamic law. Fiqh Indonesia as reflected in the Compilation of Islamic Law (KHI) in Indonesia contains important fiqh ruling, which not only represents not just the Shafi’i schools, but also madhab four. In addition, another important thing is that it contains KHI customs consideration as a legal basis so that the product appears Gono-gini fiqh treasures which are clearly different to the treasures of fiqh outside Indonesia. Basing on the ’urf is based on the fact that the law change with time, place and circumstances.